Pediatric Inflammatory Multisystem Syndrome and Rheumatic Diseases During SARS-CoV-2 Pandemic - Adrien Schvartz; Alexandre Belot; Isabelle Kone-Paut (Frontiers Media S.A., 2020)
Globally, the coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), appeared to have a milder clinical course in children compared to adults. As severe forms of COVID-19 in adults included an aberrant systemic immune response, children with chronic systemic inflammatory diseases were cautiously followed. No evidence for a specific susceptibility was identified in this pediatric population. European and US Pediatricians started to notice cases of myocarditis, sharing some features with toxic shock syndrome, Kawasaki disease, and macrophage activation syndrome in otherwise healthy patients. Multisystem Inflammatory Syndrome in Children (MIS-C) and Pediatric Inflammatory Multisystem Syndrome (PIMS) have designated this new entity in the US and Europe, respectively. The spectrum of severity ranged from standard hospitalization to pediatric intensive care unit management. Most patients had a clinical history of exposure to COVID-19 patients and/or SARS-COV2 biological diagnosis. Clinical presentations include fever, cardiac involvement, gastro-intestinal symptoms, mucocutaneous manifestations, hematological features, or other organ dysfunctions. The temporal association between the pandemic peaks and outbreaks of PIMS seems to be in favor of a post-infectious, immune-mediated mechanism. Thus, SARS-CoV2 can rarely be associated with severe systemic inflammatory manifestations in previously healthy children differently from adults highlighting the specific need for COVID-19 research in the pediatric population.